Silent alarm: Link lifetime prediction for reliable routing in VANET - Kamaruzaman, Nur Saneiah; Hasbullah, Halabi (2009)
Transmission of silent alarm messages from a target stolen vehicle node to its final destination node, such as a Police Station, is an attempt to deter problems related to vehicle theft by exploiting the VANET technology.This paper proposed a forwarding scheme for sending silent alarm messages between any two vehicle nodes in a VANET topology based on prediction of link reliability between them.Based on this single hop link prediction, the transmission of silent alarm messages through a complete route can be expected to be efficient and safe using the platform of vehicle to-vehicle communication and vehicle-to-roadside infrastructure on a highway. Two communication scenarios are considered: when the two vehicles are moving in the same direction and when they are moving in the opposite direction to each others.The strategy for computing a reliable link is based on lifetime prediction technique.The performance of this technique for link reliability will be evaluated using MATLAB simulation.